Peran Eskalasi Komitmen Terhadap Perusahaan Tikar Mendong - rini indriani; Laras Pratiwi; Isny Deslyani; Nisrina Rihhadatul Aisy (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This research aims to describe the extent of the phenomenon of escalation of commitment to the mendong mat business in Kamulyan Village. This research is important because it provides an understanding of the escalation of commitment because the point is whether one has to maintain one's business, change one's business sector or even close one's business to avoid losses. to improve individual abilities in making more rational and objective decisions. This research uses a qualitative approach with descriptive research type. Qualitative research is research based on the philosophy of postpositivism, which views that social reality is complex and multidimensional, so it cannot be observed objectively. Based on the research results, it can be concluded that the escalation of commitment to Mr. Lukman's mendong mat business occurred due to perception bias and consideration bias. He continues to maintain his business even though there is tight market competition and a decline in turnover. This is done to avoid losses, maintain self-esteem, and avoid embarrassment. The appropriate theory to explain the escalation of commitment in this research is self-justification theory. In this case, Mr Lukman tried to justify his decision to continue running the mendong mat business, even though the business was not profitable.